Грошове забезпечення як важлива соціальна гарантія трудової діяльності військовослужбовців в Україні - Подорожній, Є. Ю.; Podorozhnii, Ye. Yu.; Подорожній, А. Ю.; Podorozhnii, A. Yu.; Подорожній Євген Юрійович; Артем Подорожній (Право.ua. - 2024. - № 1. - С. 240-245, 2024)
У статті, спираючись на аналіз наукових поглядів вчених, запропоновано авторське визначення понять «соціальні гарантії військовослужбовців» та «грошове забезпечення військовослужбовців». Узагальнено, що фінансове забезпечення є надважливим видом соціальних гарантій військовослужбовців, особливо сьогодні, коли вони кожного дня ризикують своїм життя, захищаючи громадян та територіальну цілісність нашої держави. Разом із тим, на сьогоднішній день справедливим буде говорити про те, що механізм реалізації даної гарантії є недосконалим. Зазначене обумовлено: по-перше, фінансово-економічною нестабільністю в країні; по-друге, проблемами організаційного характеру, пов’язаними із визначенням того, який саме вид фінансового забезпечення може бути застосовано до військовослужбовців в той чи інший момент несення служби.

It has been established that the social guarantees for military personnel constitute a system of measures (economic, social, organizational, etc.), as well as privileges and compensations provided to individuals performing military service or undergoing military duty, aimed at ensuring the realization of their right to a decent standard of living. It is noted that as of today, the list of social guarantees for military personnel is not clearly defined, neither at the legislative nor at the scientific levels. However, it is argued that one of the most important social guarantees in today’s conditions is the financial support for military personnel. This is explained by the fact that it: firstly, affects the well-being of the military and their families; secondly, directly influences the prestige of the military profession, as well as their socio-economic status; thirdly, enhances the attractiveness of service in the Armed Forces overall. It is argued that financial support for military personnel is a system of payments provided by the norms of current legislation for the performance of military duty. Such payments are made in monetary form and in such volume as to correspond to the conditions of military service and ensure the stability of the collective. It is summarized that financial support is a crucial type of social guarantee for military personnel, especially today, when they risk their lives every day defending the citizens and territorial integrity of our state. However, it is fair to say that the mechanism for implementing this guarantee is imperfect. This is due, firstly, to the financial and economic instability in the country; secondly, to organizational problems associated with determining which specific type of financial support can be applied to military personnel at any given moment of service.

В статье, основываясь на анализе научных взглядов ученых, предложено авторское определение понятий «социальные гарантии военнослужащих» и «денежное обеспечение военнослужащих». Обобщено, что финансовое обеспечение является важнейшим видом социальных гарантий военнослужащих, особенно сегодня, когда они каждый день рискуют своей жизнью, защищая граждан и территориальную целостность нашего государства. Вместе с тем, на сегодняшний день справедливым будет говорить о том, что механизм реализации данной гарантии несовершенен. Указанное обусловлено: во-первых, финансово-экономической нестабильностью в стране; во-вторых, проблемами организационного характера, связанными с определением того, какой именно вид финансового обеспечения применим к военнослужащим в тот или иной момент несения службы.
Keywords: соціальні гарантії; грошове забезпечення; військовослужбовці; грошова виплата; social guarantees; financial support; military personnel; monetary payment; социальные гарантии; денежное обеспечение; военнослужащие; денежная выплата